Comparative salary‐related costs of a brief app‐directed delirium identification protocol by hospitalists, nurses, and nursing assistants. Issue 8 (20th April 2022) - Leslie, Douglas L.; Fick, Donna M.; Moore, Amber; Inouye, Sharon K.; Jung, Yoojin; Ngo, Long H.; Boltz, Marie; Husser, Erica; Shrestha, Priyanka; Boustani, Malaz; Marcantonio, Edward R.
Abstract: Background: Systematic screening can improve delirium identification among hospitalized older adults. Prior studies have shown clinicians and health system leaders may believe they do not have the time and resources for assessment. We conducted a comparative salary‐related cost analysis of an adaptive delirium identification protocol directed by an iPad app. Methods: We recruited 527 older adult medicine patients from an urban academic medical center ( n = 269) and a rural community hospital ( n = 258). Physicians and nurses completed the two‐step Ultra‐brief Confusion Assessment Method (UB‐CAM) protocol (with or without a skip pattern), while certified nursing assistants completed only the UB‐2 ultra‐brief screen. The sample included 527 patients (average age 80, 57% women, 35% with dementia). Time required to administer the protocol was collected automatically by the iPad app. Salary‐related costs of screening were determined by multiplying the time required by the hourly wage for the three disciplines, as obtained from national and regional published healthcare salary cost data. Cost estimates for entire hospital implementation were also calculated. Results: Participants were screened on 924 hospital days by 399 clinicians (53 physicians, 236 nurses, 110 CNAs). For the UB‐2, CNAs cost per screen was lower than the other clinician types (0.37 per screen vs. 0.73 for nurses and 2.39 for hospitalists). For the UB‐CAM with skip (UB‐CAM), costs per protocol were 1.10 for nurses vs. 3.61 for physicians. The annual salary–related costs of hospital‐wide implementation of a nurse‐based UB‐CAM protocol in a medium‐sized (300‐bed) hospital was 63, 015 plus 4356 for initial and annual training. Conclusions: CNAs and nurses had the lowest salary‐associated costs for app‐directed CAM‐based delirium screening and identification, respectively. Salary‐related annual hospital costs for the most efficient protocols in a medium‐sized hospital were less than the annual cost of hiring 1 FTE of the discipline performing the protocols.